Industrial Archaeology at the TU Bergakademie Freiberg in Germany, in International Context - Albrecht, Helmut (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2020)
This article gives an overview about the development of the teaching and research activities in industrial archaeology at the Institute for Industrial Archaeology, History of Science and Technology at the University of Technology and Mining Academy Freiberg in Germany in international context. It outlines the international development of the new discipline of industrial archaeology from its beginning until today with a special focus on Germany. It discusses the subject area, objectives and methodology of industrial archaeology as well as its relation to industrial heritage, industrial monument preservation and industrial culture.